Linguocultural type of «gover official» in Kazakhstan media - Temirgazina, Z.K.; Belova, E.O. (KSU publ., 2020)
The article discusses the evaluative component of the linguistic and cultural type «official». At present, the theory of linguocultural characters is one of the rapidly developing areas of linguistics, since modern linguistics has accumulated significant material regarding cultural concepts and linguistic personality. Type modeling involves a phased analysis of the conceptual, figurative and evaluative components of the concept. Assessment is one of the most important linguistic categories, taking direct part in language communication. This article identifies the most important evaluative characteristics of the linguocultural type based on the analysis of value judgments. To identify and describe the estimated characteristics of the linguocultural character «official», text fragments containing an assessment of events are examined in detail. Research material was provided by the Kazakhstan media. The moral and intellectual qualities, professional characteristics are studied in detail, as well as the activity side of the personality — behavior and speech. During the study, different types of assessments were considered: ethical assessment, intellectual assessment, emotional assessment.
Keywords: linguistic and cultural character; evaluative component; official; values